(untitled) (Annals of Medical Research, 2022)
Aim: We aimed to investigate the frequency of intra-abdominal injury in posttraumatic isolated transverse process fractures (iTPF) and the factors affecting the injury, especially the effect of the size of the fracture on the injury. Materials and Methods: Patients’ age, gender, trauma type determined by Computed Tomography (CT), fracture localization, separation distance of the fracture from the vertebral body, neurological status, and non-vertebral organ injury, if any, were evaluated retrospectively. Results: Intra-abdominal injury was detected in 16 of 70 patients with iTPF included in the study. The most common cause of iTPF was falls. Those with multiple TPF had a higher rate of intra-abdominal injury. Liver injury was the most common type of intra-abdominal injury. The separation distance of iTPFs from the vertebral body was mean 5.81±1.9 mm in patients with intra-abdominal injury and 3.90±1.69 mm in patients without intra-abdominal injury, and the separation distance was statistically significantly higher in patients with intra-abdominal injury (p<0.05). Conclusion: This study showed that intra-abdominal injury may be common in cases of iTPF. The severity of the trauma, the high number of fractures, and the length of the fracture distances have caused organ damage to be seen more frequently.